The essential SOAP note in an EHR age. Issue 2 (18th February 2016) - Pearce, Patricia F.; Ferguson, Laurie Anne; George, Gwen S.; Langford, Cynthia A.
Abstract : Abstract: This article reviews the traditional Subjective, Objective, Assessment, and Plan (SOAP) note documentation format. The information in the SOAP note is useful to both providers and students for history taking and physical exam, and highlights the importance of including critical documentation details with or without an electronic health record. Abstract : This article reviews the traditional Subjective, Objective, Assessment, and Plan (SOAP) documentation format. The information is useful for both providers and students for integrating history-taking and physical exam and highlights the importance of attending to critical documentation details with or without the use of an electronic health record.